Some freshwater phytoplankton as new reports and one new forma from Bangladesh (Bangladesh Journal of Plant Taxonomy, 2010)
Eight newly recorded taxa of freshwater phytoplankton from Bangladesh have been described in the present paper. Of these, 3 species are from Cryptomonadales, 2 species from each of Volvocales and Euglenales and one species from Chromulinales. In addition one new forma of Pediastrum duplex Meyen var. duplex fa. nagdaensis M.A. Alfasane, M.S. Islam & M. Khondker fa. nov. (Chlorococcales) has also been described in this account.Keywords: Phytoplankton; Chlamydomonas; Pyramidomonas; Pediastrum; Epicystis; Chroomonas.DOI: 10.3329/bjpt.v17i1.5394Bangladesh J. Plant Taxon. 17(1): 87-92, 2010 (June)